2019
DOI: 10.4064/sm170529-31-8
|View full text |Cite
|
Sign up to set email alerts
|

Weighted mixed weak-type inequalities for multilinear operators

Abstract: In this paper we present a theorem that generalizes Sawyer's classic result about mixed weighted inequalities to the multilinear context. Let w = (w1, ..., wm) and ν = w 1 m 1 ...w 1 m m , the main result of the paper sentences that under different conditions on the weights we can obtainwhere T is a multilinear Calderón-Zygmund operator. To obtain this result we first prove it for the m-fold product of the Hardy-Littlewood maximal operator M , and also for M( f )(x): the multi(sub)linear maximal function intro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…The first proof uses the Calderón-Zygmund decomposition and is a weighted version of the proof in [16]; the second proof uses the Nazarov-Treil-Volberg method and is a weighted version of the proof in [20]. See [10] for a related result that is deduced using multilinear extrapolation. Remark 1.…”
Section: And [W]mentioning
confidence: 99%
“…The first proof uses the Calderón-Zygmund decomposition and is a weighted version of the proof in [16]; the second proof uses the Nazarov-Treil-Volberg method and is a weighted version of the proof in [20]. See [10] for a related result that is deduced using multilinear extrapolation. Remark 1.…”
Section: And [W]mentioning
confidence: 99%
“…There is no reason to restrict ourselves to the study of one-variable Sawyer-type inequalities. Quite recently, the bound (1.1) has been extended to the multi-variable setting in [40]. More precisely, for weights w 1 , .…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the conjecture of E. Sawyer in [54], we can ask ourselves if it is possible to obtain bounds like (1.8) for multi-linear Calderón-Zygmund operators T . Once again, the endpoint case p 1 = • • • = p m = 1 has already been considered and extensively investigated in [40]. There, it was shown that for weights w 1 , .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations